2017
DOI: 10.19183/how.24.1.318
|View full text |Cite
|
Sign up to set email alerts
|

The Socialization of a Novice Teacher of English: Becoming an Agent of Change

Abstract: This case study reports the analysis of the induction as a socialization process of a Colombian novice teacher of English. Since critical approaches to socialization highlight the role of novice teachers in critical school transformation during their induction stage, this study aims to disclose the teacher's possibilities of becoming an agent of change. The data collection procedures included interviews, class observations and document analysis. The findings revealed that the teacher's socialization was not a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
1
0
3
Order By: Relevance
“…En este sentido, el 64,9 % de los artículos abordan el objeto de estudio de forma central (más del 80 % del contenido del artículo refiere al objeto de estudio), bien sea mediante comparativa de programas o medidas, análisis de políticas y/o legislaciones, agentes intervinientes en los procesos, descripción de experiencias y programas nacionales o específicos y casos únicos (Boerr 2018;Castillejo et al, 2017;Colazzo & Cardozo, 2021;de André, 2012;Flores., 2014;Gomes et al, 2021;González et al, 2019;Gorichon et al,2020;Jáspez & Sánchez, 2019;López & Marcelo, 2018Marcelo García et al, 2016a, 2016bMarcelo & Vaillant, 2017;Marcelo & López, 2020;Mesa, 2017;Reséndiz, 2019;Rodríguez & Márquez, 2021;Rozas & Vergara, 2013;Salas et al, 2021;Silva & Moreira, 2021;Vaillant, 2021).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…En este sentido, el 64,9 % de los artículos abordan el objeto de estudio de forma central (más del 80 % del contenido del artículo refiere al objeto de estudio), bien sea mediante comparativa de programas o medidas, análisis de políticas y/o legislaciones, agentes intervinientes en los procesos, descripción de experiencias y programas nacionales o específicos y casos únicos (Boerr 2018;Castillejo et al, 2017;Colazzo & Cardozo, 2021;de André, 2012;Flores., 2014;Gomes et al, 2021;González et al, 2019;Gorichon et al,2020;Jáspez & Sánchez, 2019;López & Marcelo, 2018Marcelo García et al, 2016a, 2016bMarcelo & Vaillant, 2017;Marcelo & López, 2020;Mesa, 2017;Reséndiz, 2019;Rodríguez & Márquez, 2021;Rozas & Vergara, 2013;Salas et al, 2021;Silva & Moreira, 2021;Vaillant, 2021).…”
Section: Resultsunclassified
“…Finalmente, (C5) artículos que ponen el énfasis en experiencias únicas de inducción aplicadas a un centro educativo concreto y/o persona (de Medeiros et al, 2018;León, 2016;Mesa, 2017). Si bien no todos los artículos poseen un enfoque comparativo, al acotar la investigación a una gran demarcación geográfica, la región latinoamericana, se ha considerado útil y conveniente emplear la clasificación de los estudios en función de las unidades de la comparación que realiza (Garcia-Garrido, 1982 en base a Le Thanh Khoi, 1981) y que los categoriza en supranacionales, internacionales e intranacionales.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Therefore, empirical evidence about novice teachers are quite limited, contrary to the data concerning experienced and professional teachers, which is abundant as has been reviewed by Widiati, Suryati, and Hayati (2017), some of which are, for example, studies by Musthofa (2011), Triyanto (2012, Abdullah (2015), and Irmawati and Widiati (2017). Meanwhile, at the international context, much research on novice teachers has revealed that the initial years of teaching are often marked with confusion, challenges, and tensions (see, e.g., Jin et al, 2019;Liu, 2014;Mann & Tang, 2012;Mesa Villa, 2017;Senom, Zakaria, & Shah, 2013). Referring to this phenomenon, in 2017 we proposed a 3-year research project to the Indonesian Ministry of Research, Technology, and Higher Education on the empowerment of novice English teachers, with three main objectives: unraveling the challenges of novice Indonesian teachers of English, developing a booklet for professional development (PD) in response to the problem areas that have been identified, and measuring the effectiveness of the booklet.…”
Section: Introductionmentioning
confidence: 99%